Adaptive change of land use to nature and society in China's agro-pastoral ecotone. (March 2023) - Geng, Xin; Hu, Shi; Wang, Xunming; Cai, Diwen; Gong, Yuan
Abstract: Land use and cover change (LUCC), as an adaptation and confrontation of landowners to environmental changes, plays an essential role in supporting multiple goals of sustainable development. However, the driving process and prospects of LUCC remain unclear at the regional scale. Using remote sensing methods, trend analysis, binary logistic regression models and open-scenario-based forecasting, this study explored the spatio-temporal pattern and driving factors of LUCC in the agro-pastoral ecotone of northeast China (APENE) from 2001 to 2018, revealed potential risks in land-use patterns and key issues in current policies, and proposed targeted suggestions. Results showed that over the past two decades, the areas of forest and farmland increased by 67.55 % and by 31.64 % and that of grassland decreased by 14.58 % via the transition from farmland to grassland, grassland to farmland, and grassland to forest in the mode of edge expansion in the APENE, with 60.76 % areas were greening, while 1.04 % browning. The driving force of LUCC varied greatly with space and land use type, and natural factors play dominant roles in LUCC in the APENE. Over 70 % of farmland might be abandoned under the impact of future climate change, and serious conflict between afforestation investment and forest adaptation. The lack of scientific regulation of farmland quality and ecosystem adaptability were major problems in current policies. More positive economic and regulatory policies to benefit farmers and foresters should be adopted to further improve the talent and financial attractiveness of the agricultural production and desertification-combating practices and to fundamentally solve the current dilemma of food security and ecological construction. Graphical Abstract: ga1 Highlights: LUCC and its greening effect was investigated in the APENE. Natural factors dominate LUCC in APENE based on proposed binary logistic regression models. Current agriculture and afforestation practices may face dilemmas under future climate change. Current policies lack scientific regulation of farmland quality and ecosystem adaptability. More positive economic and regulatory policies to benefit farmers and foresters should be adopted.